Processo grupal na formação de coordenadores de grupo - Scola, Lourdes Sgarabotto (2013)
This dissertation consists of two parts and aims to increase the knowledge of groups from the analysis of the group process. In the first part - Group Process in small groups - group concepts are presented, of the group process, theoretical operators, according to traditional and current authors for the theme have proposed and that influence the study and practice of group work currently. To discuss the group process aboard six aspects - openness, learning, resistance to change, interpersonal feedback, links reconfiguration, coordination - that are articulated with the principles of complex systemic thinking. In the second part - Group process in a training group of group coordinators - the results of the empirical research are presented, that generally aimed to understand how the group process occurred in a group of a course that trains students for careers coordinating groups. This is a qualitative study, transverse, composed by documentary research reports written by participants, as well as the field diary of one of the course coordinators. For data understanding, it was used Textual Analysis of Discourse strategy. Among the main results, stands out: (a) the opening as the first more expressive movement in the group process, followed by the resistance to change; (b) the interchangeable presence of these two categories on a frequent way, on a movement of surface/deepness; (c) the opening favored the appreciation of the individual learning and of the group process experienced: the group became a learning field. It s concluded that the process experienced by the group was of opening, resistance to change and learning, and the interpersonal feedback was the thread that promoted the movement, the overcoming of the challenges and favored the achievement of group goals